2021
DOI: 10.3389/fmicb.2021.651711
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sub-Lethal High Pressure Homogenization Treatment on the Adhesion Mechanisms and Stress Response Genes in Lactobacillus acidophilus 08

Abstract: Cell surface hydrophobicity (CSH) and adhesion are very important phenotypical traits for probiotics that confer them a competitive advantage for the resilience in the human gastrointestinal tract. This study was aimed to understand the effects over time of a 50 MPa hyperbaric treatment on the surface properties of Lactobacillus acidophilus 08 including CSH, autoaggregation, and in vitro adhesion (mucin layer and Caco-2 cells). Moreover, a link between the hurdle applied and the expression of genes involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…The wines obtained from HPH-treated strains had significantly modified ester profiles, with lower concentrations of those compounds with medium-and long-chain fatty acids For example, some authors have hypothesized how HPH, when applied to bacteria or yeast cells at levels ranging between 50 and 100 MPa, induces changes in gene expression that regulate specific properties (such as autolysis or production of aroma compounds) without affecting the cell viability or the fermentation kinetics [61][62][63][64]. In addition, to modify their metabolism, the application of HPH at a sub-lethal level was suggested also to modify some functional properties of lactic acid bacteria to be used in the dairy sector, with such exposure of protein hydrophobic regions in the cell wall resulting in different autoaggregation and adhesion capacities [65]. In the oenological field, Patrignani et al [62] showed that an HPH treatment applied at 90 MPa to different yeasts (Saccharomyces bayanus L951 and S. cerevisiae ML692 and commercial strains S. bayanus Lalvin CH14, S. bayanus IOC 18-2007, S. bayanus Lalvin EC1118, and S. bayanus IT 1818), prior to use or prior to their use in the preparation of tirage solutions for sparkling wines, induced an acceleration of yeast autolysis with a consequent release of mannoproteins and different patterns in volatile profiles.…”
Section: Effect Of Non-thermal Technologies On the Production Of Wine...mentioning
confidence: 99%
“…The wines obtained from HPH-treated strains had significantly modified ester profiles, with lower concentrations of those compounds with medium-and long-chain fatty acids For example, some authors have hypothesized how HPH, when applied to bacteria or yeast cells at levels ranging between 50 and 100 MPa, induces changes in gene expression that regulate specific properties (such as autolysis or production of aroma compounds) without affecting the cell viability or the fermentation kinetics [61][62][63][64]. In addition, to modify their metabolism, the application of HPH at a sub-lethal level was suggested also to modify some functional properties of lactic acid bacteria to be used in the dairy sector, with such exposure of protein hydrophobic regions in the cell wall resulting in different autoaggregation and adhesion capacities [65]. In the oenological field, Patrignani et al [62] showed that an HPH treatment applied at 90 MPa to different yeasts (Saccharomyces bayanus L951 and S. cerevisiae ML692 and commercial strains S. bayanus Lalvin CH14, S. bayanus IOC 18-2007, S. bayanus Lalvin EC1118, and S. bayanus IT 1818), prior to use or prior to their use in the preparation of tirage solutions for sparkling wines, induced an acceleration of yeast autolysis with a consequent release of mannoproteins and different patterns in volatile profiles.…”
Section: Effect Of Non-thermal Technologies On the Production Of Wine...mentioning
confidence: 99%